Nutrient Potency of Rice Straw Processed with Amofer as Cattle Feed Stuff in East Kalimantan - Hamdi Mayulu; Suhardi Suhardi (International Journal of Science and Engineering, 2015)
Forage demand can be supplied from rice straw which processed with certain feed technology innovation. Some advantages can be derived under this technology i.e. increasing nutrient content, optimizing the utilization, improving the efficiency and reducing production cost by minimizing feed cost. Ammoniation fermentation (amofer) as an applied technology could give solution over the limitation of rice straw availability. The objective of this research was to determine the potency of rice straw processed with amofer (amofer-rice straw) as raw material to formulate complete feed. The experiment was carried out with randomized block design with three treatments and six replications. Amofer treatment was carried out by adding urea 3% from the total material and then placed into plastic jar +12 liter and then incubated under an-aerobic process for 18 days. Fermentation material i.e. biology starter by 1% of total material was added at the ninth day. Dry Matter (DM) content resulted from each treatments was 87,28%, 85,96% and 84,61% for T1, T2 and T3, respectively. Crude Protein (CP) content was T1=24,48%, T2=21,04%; and T3=24,46%, Crude Fiber (CF) content was T1=31,30%; T2=31,30%; and T3=31,39%. Total Digestible Nutrient (TDN) for version 1 was  T1=57,29; T2=56,19; and T3=56,89 and version 2 was T1=53,11%; T2=52,28%; and T3=51,10%. The average value of Non Nitrogen Free Extract (NNFE) was T1=23,49%; T2=28,08%; and T3=26,57%. The utilization of amofer as applicable technology is considered as the most appropriate method to increase the quality of rice straw by significantly increase nutrient content in term of crude protein (CP) and reduce crude fiber (CF) content. This increasing quality can be seen from the result of proximate analysis, NNFE and TDN content